The practice of public art - Cartiere, Cameron; Willis, Shelly (New York : Routledge, 2008)
Coming in from the cold: a public art history / Cameron Cartiere ## Time in place: new genre public art a decade later / Suzanne Lacy ##Space, place and site in critical spatial arts practice / Jane Rendell ##"Be a crossroads": public art practice and the cultural hybrid / Margaret Adamek and Karl Lorenz##Critical spaces: monuments and changes / Malcolm Miles ##oward a celebratory and liberating system of teaching public art / Stephanie Anne Johnson ## fine public art & design education: learning and teaching public art / Faye Carey ##Public art and education: an interview with Harrell Fletcher / Shelly Willis ##The millennium park effect: a tale of two cities / Regina M. Flanagan ##Investigating the public art commissioning system: the challenges of making art in public / Shelly Willis ##Here and gone: making it happen / Kristin Calhoun and Peggy Kendellen ## rich as getting lost in Venice: sustaining a career as a public artist in the public realm / Terri Cohn ##From margin to mainstream: dyke action machine! Public art and a Recent history of lesbian representation / Carrie Moyer ##In the storms of the world: building communities to assist social and ecological justice / James Marriott ##The art of the question: thinking like a public artist / Anonymous ##A timeline for the history of public art: the United Kingdom and the United States of America, 1900-2005 / Cameron Cartiere, Rosemary Shirley, and Shelly Willis.
boek